PENGARUH PENERAPAN STANDAR OPERASIONAL PROSEDUR DAN DISIPLIN KERJA TERHADAP KINERJA: KEPUASAN KERJA SEBAGAI VARIABEL MEDIASI - Amelia Cindy Cahya Adisty; M. Farid Wajdi (POLITEKNIK LP3I JAKARTA, 2024)
This study aims to analyze the influence of Standard Operating Procedures (SOP) implementation and work discipline on employee performance with job satisfaction as a mediating variable at PT. Paragon Technology and Innovation. The research employs a quantitative approach with purposive sampling technique. Data were collected through questionnaires distributed to 85 employees. Data analysis uses Structural Equation Modeling (SEM) with SmartPLS. The results show that: (1) SOP has a negative insignificant effect on employee performance, (2) Work discipline has a significant positive effect on employee performance, (3) SOP has a significant positive effect on job satisfaction, (4) Work discipline has a significant positive effect on job satisfaction, (5) Job satisfaction has a significant positive effect on employee performance, (6) Job satisfaction cannot mediate the relationship between SOP and employee performance, and (7) Job satisfaction can mediate the relationship between work discipline and employee performance.